Diagnosis of Endometrial Tuberculosis in Two Women who Underwent Assisted Reproductive Treatment for Bilateral Tubal Factor Infertility: Case Report - Sahin, Levent; Albayrak, Mustafa; Celik, Ebru; Sema Ozkan, Zehra; Artas, Gokhan; Kumbak Aygun, Banu (Annals of Medical Research, 2021)
None